2010
DOI: 10.1097/icl.0b013e3181c7bda6
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Daily Symptoms Associated With the Silicone Hydrogel Contact Lens Wear

Abstract: Daily wear symptoms associated with lotrafilcon B CL increase with the time of wear. This increase in symptoms is nonrelated with the multipurpose solutions compared in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Signs such as conjunctival hyperaemia and papillae also show no association with SICS/PATH. Although longer and larger studies may add some clarity around the presence or absence of an association of SICS/PATH and symptoms, the clear consensus at the present time is that no such association exists …”
Section: Signs and Symptoms Of Sics/pathmentioning
confidence: 86%
See 1 more Smart Citation
“…Signs such as conjunctival hyperaemia and papillae also show no association with SICS/PATH. Although longer and larger studies may add some clarity around the presence or absence of an association of SICS/PATH and symptoms, the clear consensus at the present time is that no such association exists …”
Section: Signs and Symptoms Of Sics/pathmentioning
confidence: 86%
“…Based on the findings of this review in conjunction with a large body of data, there are several important differences between NaFl corneal staining in pathological situations and those observed in subjects with SICS, suggesting that this form of staining can be largely explained by PATH. Furthermore, it appears that SICS/PATH largely represents a benign artifact, rather than the pathological corneal staining seen during contact lens complications.…”
Section: Preservative‐associated Transient Hyperfluorescence As a Parmentioning
confidence: 99%
“…Symptoms associated with CL were found to increase throughout the day in some type of lenses. 7 Ocular symptoms are the main causes of CL dissatisfaction and discontinuation. 8 The primary reasons of CL discontinuation were found to be discomfort, dryness and red eyes.…”
Section: Introductionmentioning
confidence: 99%
“…The refitting of hydrogel contact lens wearers with silicone hydrogel lenses has also been reported to reduce the proportion of wearers experiencing symptoms. 15 Interestingly, several studies have found no association between contact lens-related symptoms and the type of LCP, 14,16 although lens care manufacturers have modified their products to increase contact lens comfort. 17 Conversely, several studies have shown that the lens type/LCP combination may affect comfort because certain combinations performed better in subjective responses when compared with others.…”
mentioning
confidence: 99%